Retroperitoneal Tumors Clinical Management (Springer Netherlands, 2018)
This book provides a comprehensive, state-of-the-art review of the diagnosis and management of retroperitoneal tumors. It highlights current surgical techniques for combined resection and reconstruction of various abdominal and pelvic organs and structures, along with adjuvant therapy. The book consists of three parts: Part 1 summarizes basic knowledge on retroperitoneal tumors and provides a detailed introduction to diagnosis and treatment, while Part 2 focuses on the surgical techniques used for retroperitoneal tumors and describes general procedures for operations on retroperitoneal tumors at different sites. Lastly, Part 3 details the etiology, pathology, evaluation, treatment and prognosis of retroperitoneal tumors according to pathological subtypes. This book is designed as a resource and guide for surgical and medical oncologists working with retroperitoneal tumors. Cheng-Hua Luo, MD, PhD, is a professor of surgery and the director of the department of retroperitoneal tumors surgery, Peking University International Hospital, China.